2022
DOI: 10.13057/biodiv/d230458
|View full text |Cite
|
Sign up to set email alerts
|

The potency of selected ethnomedicinal plants from East Kalimantan, Indonesia as antidiabetic agents and free-radical scavengers

Abstract: Abstract. Ramadhan R, Phuwapraisirisan P, Amirta R, Darmawan MFB, Ul-Haq K, Kusuma IW, Suwito H, Abdulgani N, Mukhdlor A, Saparwadi. 2022. The potency of selected ethnomedicinal plants from East Kalimantan, Indonesia as antidiabetic agents and free-radical scavengers. Biodiversitas 23: 2225-2231. Ten ethnomedicinal plant extracts from East Kalimantan flora, traditionally used to treat blood sugar levels and other diabetes-related diseases, were examined in vitro for their antidiabetic and free radical scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This result is correlated with its traditional use as antidiabetic. A similar study also conducted by Ramadhan (2022) confirmed the ethnopharmacological use of selected plants from East Kalimantan might have potential as an antidiabetic and natural antioxidant. This study has limitations on the interpretation of the pharmacological activity and phytochemical compounds of all cited plants.…”
supporting
confidence: 59%
“…This result is correlated with its traditional use as antidiabetic. A similar study also conducted by Ramadhan (2022) confirmed the ethnopharmacological use of selected plants from East Kalimantan might have potential as an antidiabetic and natural antioxidant. This study has limitations on the interpretation of the pharmacological activity and phytochemical compounds of all cited plants.…”
supporting
confidence: 59%
“…The α-glucosidase inhibitory activity of Diospyros sp. extract was examined using the chromogenic method described by Ramadhan et al (2022) with slight modification. Briefly, various concentrations of extract (20 μL) were added with a phosphate buffer with pH 6.8, followed by 50 μL of α-glucosidase.…”
Section: In Vitro Antidiabetic Activity α-Glucosidase Inhibition Assaymentioning
confidence: 99%
“…East Kalimantan is renowned for its biodiversity and natural resources, including aromatic plants and medicinal plants. The potential of East Kalimantan's medicinal plants and essential oils has been extensively researched, including its potential to be developed as antioxidants, antibacterials, anticancer agents, and other substances (Kuspradini et al 2019;Ramadhan et al 2022). However, using plants as essential oils that originate from East Kalimantan has been widely practiced.…”
Section: Introductionmentioning
confidence: 99%